Agricultura familiar em comunidade amazônica: usos da terra e estratégias de produção agrícola no Jagarajó em Ponta de Pedras, Pará - ANDRADE, Edinaldo Teles de (2022)
This final paper proposes to discuss the importance of family farming in the community of Jagarajó, on the municipality of Ponta de Pedras, Estate of Pará. The proposal is to comprehend how the relation between society and the space where their activities are made is built, besides highlighting topics such as work relations and cultural practices. It is perceived how the community has been generating an agriculture of socioeconomic importance for the local families, because farming is the main economical activity and food base, where the land’s forms of usage and production still search for balance between land and labor, with few transformations regarding the planting techniques. Thus, the objective is to show how family farming is configured in the community, describing its characteristics as well as paying attention to the importance of the heart of the city of Ponta de Pedras. It was found that farmers face difficulties both in increasing their production and in expanding the purchase market for their products.